Reaping the Benefits of Deeper Euro-Med Integration Through Trade Facilitation - Yves Bourdet; Maria Persson (Research Institute of Industrial Economics (IFN), 2011)
The current political turmoil in the Arab world has contributed to renewed interest in the Barcelona Process. This paper explores whether deeper integration in the form of trade facilitation - i.e. improved and simplified trade procedures - could be an important part of a reform agenda. Adopting a Southern perspective by focusing on exports from non-EU Mediterranean countries to the EU, we test whether the efficiency of trade procedures affects (i) bilateral volumes of exports, and (ii) the number of products exported. Our findings suggest that trade facilitation could lead to substantially increased export volumes and export diversification.
Keywords: F15; O19; O24; 330; Barcelona Process; Mediterranean Union; European Union; Deeper Integration; Trade Facilitation; Export volumes; Export Diversification; Handelsliberalisierung; Exportdiversifizierung; Panel; Mittlerer Osten; Nordafrika; EU-Staaten